2013
DOI: 10.1111/luts.12011
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the King's Health Questionnaire for Male Lower Urinary Tract Symptoms in Taiwan

Abstract: Objectives: The aim of this study is to evaluate the psychometric properties of the Iranian version of the Quality of Life (QoL) questionnaire in patients with urinary incontinence (UI). Methods: The English questionnaire on lower urinary tract symptoms was initially translated into Persian, and then back-translated into English. Final modifications were made after testing the questionnaire on Iranian patients with UI. To validate the translated questionnaire, the following tests were undertaken: content/face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The factor loadings ranged from 0.499 to 0.898 for Factor 1 and from 0.339 to 0.937 for Factor 2. Although the factor loading of the item related to the domain General health perception was below 0.40, we decided to keep it because the literature also reported values very close to those found here (Huang et al, 2014;Okamura et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The factor loadings ranged from 0.499 to 0.898 for Factor 1 and from 0.339 to 0.937 for Factor 2. Although the factor loading of the item related to the domain General health perception was below 0.40, we decided to keep it because the literature also reported values very close to those found here (Huang et al, 2014;Okamura et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…Concerning the structural analysis of the instrument, it should be noted that the original author (Kelleher et al, 1997) did not present those results in his study. Two studies (Huang et al, 2014;Okamura et al, 2009) with women and men with urinary symptoms found a three-factor structure. Despite the divergence about the data in the literature, the two-factor structure found here showed satisfactory fit indices (Damásio, 2012), which supports the structural validity of the instrument in this population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations